Innovative strategy making in higher education - Martinez, Mario, 1967-; Wolverton, Mimi (Emerald Publishing Limited : Information Age Publishing, 2009)
The purpose of this book is to offer higher education leaders, scholars, consultants, and observers a full range of strategy tools that can be applied to the higher education industry. This is accomplished by a) introducing new concepts and tools to give a comprehensive view of strategy making in higher education, beyond strategic planning, b) demonstrating the value of the concepts and tools through description and application for different types of institutions (universities, community colleges, for-profit colleges, etc.) and at different levels within institutions (institutional, college, department, etc.), and c) providing guidance on the appropriate uses of the various tools. The last point is especially important, as applying business-like principles to higher education often receives heavy criticism. The book helps readers decipher the appropriate uses of different strategy tools to the higher education industry, but the book also points out dangers and weaknesses. All of this is done within today's context of political, economic, demographic, and global realities.